Exploration of Salam Leaf Extract (Syzygium polyanthum) as a Natural Indicator for Acid-Base Titration: Color Stability and Endpoint Accuracy - Nasirsah, Nasirsah; Fatma, Fatma Suryani Harahap; Siregar, Rabiyatul Adawiyah; Siregar, Elda Sari; Tuah, Sahlan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Acid-base indicators play an important role in titration, but the use of synthetic indicators such as phenolphthalein is increasingly criticized for being toxic, carcinogenic, and environmentally unfriendly. Therefore, this study was conducted with the aim of developing bay leaf extract (Syzygium polyanthum) as a safer, natural indicator, thereby supporting the concept of green chemistry. The study was carried out in four stages, namely first, extraction with ethanol: water solvent (70:30 and 50:50), second, color change test in pH 4, 7, and 10 buffer solutions using visual documentation and UV-Vis spectrophotometry. Third, validation of effectiveness in HCl–NaOH titration with phenolphthalein as a comparator. Additionally, stability and reproducibility tests were conducted over a 7-day storage period. The results showed that bay leaf extract remained stable for at least seven days, exhibiting a significant λmax change profile at 405–425 nm, which varied according to pH changes. This indicates the sensitivity of phenolic pigments to acidic, neutral, and basic conditions. In titration validation, the extract with 50/50 solvent showed an identical titrant volume to phenolphthalein (25.0 mL; deviation 0%), while the 70/30 solvent showed a deviation of -14.6%. Stability tests showed that the extract was relatively stable for up to 7 days in dark conditions with a decrease in absorbance <10%, while reproducibility tests produced inter-user variations <5%. These findings suggest that bay leaf extract has strong potential as a reliable, stable, and consistent natural indicator, making it a worthy alternative to synthetic indicators in environmentally sustainable chemistry education and research laboratories.